On the Metal‐Leaf Decorations of Post‐Byzantine Greek Icons. (6th April 2017) - Mastrotheodoros, G. P.; Beltsios, K. G.; Bassiakos, Y.; Papadopoulou, V.
Abstract : Metal leaves were widely used as decorative materials in post‐Byzantine ritual painting. Fifty‐two icons (mid‐15th to mid‐19th centuries) were studied by means of analytical techniques in order to reveal the materials and techniques encountered in their metal‐leaf decorations. High‐purity gold leaf was used throughout the studied period. Silver was employed rarely and mostly during the latter part of the period in consideration, while metal powders were mostly used from the mid‐18th century onwards. The identification of a gold–silver powder mixture and an 'electrum'‐type alloy are among the reported findings, which are novel for post‐Byzantine icons. Three micromorphologically distinct highlighting techniques were also documented.